Development of Transportation System in Order to Increase Local Revenue in Banjar City - Rd Dita Prahesti Nurjanah; Zahra Puspita (Publikasi Indonesia, 2025)
The Banjar City Government has been working to improve the transportation system through road construction and the provision of public transport. An effective transportation system is key to supporting sustainable urban development. Banjar City has a strategic position on the cross-province route so that it can utilize this potential to improve connectivity with other regions. This study investigates the effectiveness of the transport system in Banjar City, focusing on its role in supporting community mobility and economic growth. The research was conducted over a period of six months, starting after approval of the research proposal and completion of the necessary permits. The main research questions included evaluating the effectiveness of the transport system in facilitating mobility and economic development, as well as identifying factors that influence the successful development of the transport system in the region. The theoretical implications of this research aim to contribute to the advancement of knowledge in the field of transport, providing insights that can enhance understanding and inform future developments. The concept of effectiveness is central to this research, defined as the extent to which predetermined objectives are achieved, with higher effectiveness indicated by outcomes aligned with these objectives. The findings are expected to offer valuable recommendations to policy makers and stakeholders involved in transport planning and development, ultimately leading to an improved transport system that better serves the needs of society and supports economic growth.